Insights Into Insect Vector Transmission and Epidemiology of Plant-Infecting Fijiviruses - Zhang, Lu; Wu, Nan; Ren, Yingdang; Wang, Xifeng (Frontiers in Microbiology, 2021)
Viruses in genus Fijivirus (family Reoviridae) have caused serious damage to rice, maize and sugarcane in American, Asian, European and Oceanian countries, where seven plant-infecting and two insect-specific viruses have been reported. Because the planthopper vectors are the only means of virus spread in nature, their migration and efficient transmission of these viruses among different crops or gramineous weeds in a persistent propagative manner are obligatory for virus epidemics. Understanding the mechanisms of virus transmission by these insect vectors is thus key for managing the spread of virus. This review describes current understandings of main fijiviruses and their insect vectors, transmission characteristics, effects of viruses on the behavior and physiology of vector insects, molecular transmission mechanisms. The relationships among transmission, virus epidemics and management are also discussed. To better understand fijivirus-plant disease system, research needs to focus on the complex interactions among the virus, insect vector, insect microbes, and plants.